2004
DOI: 10.1152/ajpgi.00009.2004
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP-3 activates TGF-β receptors and directly inhibits growth in human intestinal smooth muscle cells

Abstract: We have shown that human intestinal smooth muscle cells produce IGF-I and IGF binding protein-3 (IGFBP-3). Endogenous IGF-I acts in autocrine fashion to stimulate growth of these cells. IGFBP-3 inhibits the binding of IGF-I to its receptor and thereby inhibits IGF-I-stimulated growth. In several carcinoma cell lines and some normal cells, IGFBP-3 regulates growth independently of IGF-I. Two mechanisms for this effect have been identified: IGFBP-3 can directly activate transforming growth factor-β (TGF-β) recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…At the intracellular level this may either involve modulation of the bcl-2/bax ratio [22] or the p53 protein [23] . Kuemmerle et al, reported that endogenous IGFBP-3 directly inhibits proliferation of human intestinal smooth muscle cells by activation of TGF-betaRI and Smad 2, an effect which is independent of its effect on IGF-1 stimulated growth [24] . Interestingly, IGFBP-3 has been localized in the nucleus, implying a more direct transcriptional regulatory role, but it remains largely unknown how extracellular IGFBP-3 enters the cell [25] .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…At the intracellular level this may either involve modulation of the bcl-2/bax ratio [22] or the p53 protein [23] . Kuemmerle et al, reported that endogenous IGFBP-3 directly inhibits proliferation of human intestinal smooth muscle cells by activation of TGF-betaRI and Smad 2, an effect which is independent of its effect on IGF-1 stimulated growth [24] . Interestingly, IGFBP-3 has been localized in the nucleus, implying a more direct transcriptional regulatory role, but it remains largely unknown how extracellular IGFBP-3 enters the cell [25] .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…IGFBP-3 has been also shown to enhance Smad-2 and Smad-3 phosphorylation induced by TGF-activation of T RII, and to activate the PAI-1 promoter (Fanayan et al 2000(Fanayan et al , 2002. Furthermore affinity labeling studies of T Rs have showed that IGFBP-3 displaced binding of iodinated TGF-to T RII and stimulated Smad-2 phosphorylation (Kuemmerle et al 2004). IGFBP-3 has been also shown to bind the latent TGF-binding protein-1, although the functional significance of this binding remains unclear (Gui & Murphy 2003).…”
Section: Figure 11mentioning
confidence: 99%
“…5,7,8 Besides its IGF-I-dependent function, IGFBP-3, like IGFBP-1 and IGFBP-5, has IGF-I-independent anti-proliferative and pro-apoptotic effects. 9 The bioactivity of IGF system is modulated by retinoids, which not only decreases directly the level of IGF-1 10 but also increases IGFBP-3. 11,12 IGFBP-3, in turn, mediates a wide variety of growth suppression signals, including retinoic acid.…”
Section: Introductionmentioning
confidence: 99%